KESADARAN, ASOSIASI, PERSEPSI KUALITAS, LOYALITAS MEREK DAN KEPUTUSAN PEMBELIAN KOPI TUBRUK GADJAH (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to investigate the impact of brand awareness, brand association, quality perception, and brand loyalty on consumer purchasing decisions, with a special focus on Kopi Tubruk Gadjah. The study aims to contribute to marketing theory and practice, providing insights for marketers and enriching general marketing knowledge. This document covers theoretical foundations of branding, brand equity, and brand strategies, as well as research methodology, data collection and analysis techniques, company profiles, and characteristics of respondents involved in the study.
Keywords: Brand Awareness; Brand Association; Perceived Quality; Brand Loyalty; Consumer Purchase Decision; Marketing Theory; Brand Equity; Brand Strategy; Gadjah Kopi Tubruk